2021
DOI: 10.1111/imj.15421
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of medical education on spirituality

Abstract: Background Spirituality is a fundamental dimension of our human nature that impacts on medical care and yet is relatively neglected by medical education courses in Australia. Aim This systematic review was conducted to assess the curriculum content currently used to develop medical student understanding of, and engagement with, spirituality in the context of patient care. Methods Studies published in English from 2010 to the review date were included in order to focus on the most recent curricula. Studies incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…Appleby et al concluded their review by stating that if agreed it is desirable to encourage the integration of this dimension in general practice, we have to find common frameworks for these discussions [ 46 ], and a recent study amongst Scottish GPs even suggested to define a gold standard [ 47 ]. Wenham et al in a review proposed core content, aims and objectives to guide further work on this [ 48 ]. We recommend research on ways of warranting integration of this dimension in care for palliative patients, without disregarding the GP as a professional in a personalised approach.…”
Section: Discussionmentioning
confidence: 99%
“…Appleby et al concluded their review by stating that if agreed it is desirable to encourage the integration of this dimension in general practice, we have to find common frameworks for these discussions [ 46 ], and a recent study amongst Scottish GPs even suggested to define a gold standard [ 47 ]. Wenham et al in a review proposed core content, aims and objectives to guide further work on this [ 48 ]. We recommend research on ways of warranting integration of this dimension in care for palliative patients, without disregarding the GP as a professional in a personalised approach.…”
Section: Discussionmentioning
confidence: 99%
“…The aims and objectives of our program cited earlier are similar to those defined for the educational programs introduced at medical universities in United States, South America, United Kingdom and some other European countries ( 24 – 27 , 31 39 ). These different spirituality curricula are generally focused on improving the student mindfulness, compassion and empathy, careful listening and communication on what is integral to the person, what he/she believes in, and hopes for.…”
Section: Discussionmentioning
confidence: 99%
“…Programs concentrating on improving the ability to perform spiritual care are usually based on case discussions, real patient history taking or self-reflective journaling ( 27 ). These complement the structured clinical knowledge achieved in a medical degree and are an important component of holistic mastery in clinical medicine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations